(untitled) (Eurasian Medical Research Periodical, 2024)
The problem of neuroinfection in children is particularly relevant due to its high proportion in the structure of neurological diseases. As a result of the diffuse inflammatory process of the brain substance, severe neurological complications arise, and there is a delay in the rate of development of the functional systems of the brain that provide such integrative functions as memory, attention, thinking and other types of higher mental activity. Cognitive processes underlie the acquisition of school skills: reading, writing, counting, etc